A COMPARATIVE SYNTACTIC ANALYSIS OF RELIGIOUS PROVERBS IN ENGLISH AND UZBEK (Modern education and development, 2025)
This study explores the syntactic and grammatical features of religiously-themed proverbs in English and Uzbek, focusing on the use of imperative, infinitive, conditional, and subjectless sentence structures. While both languages employ these structures to convey religious and moral messages, their usage and grammatical realization differ significantly due to typological and cultural distinctions. English proverbs tend to favor fixed structures with explicit subjects and articles, while Uzbek proverbs make extensive use of elliptical, subjectless, and generalized-person constructions. By analyzing these patterns, the research highlights the linguistic embodiment of religious and ethical worldviews, showing how grammar acts as a reflection of societal values and collective consciousness.